Expanding role of deoxyribonucleic acid-sensing mechanism in the development of lifestyle-related diseases - Nishimoto, Sachiko; Sata, Masataka; Fukuda, Daiju (Frontiers in Cardiovascular Medicine, 2022)
In several lifestyle-related diseases, such as cardiovascular, metabolic, and respiratory diseases, chronic inflammation plays an important role in their pathogenesis. Cardiometabolic disorders share sterile chronic inflammation as a major cause; however, the exact mechanisms that are involved remain unknown. Previous studies have confirmed the damage of the vasculature and tissue of the metabolic organs in diabetes and hyperlipidemia, suggesting the possibility of leakage and/or accumulation of nucleic acids from damaged cells. Undamaged DNA is an integral factor for the sustenance of life, whereas DNA fragments, especially those from pathogens, are potent activators of the inflammatory response. Increasing evidence suggests that DNA-sensing mechanisms, which participate genetically in self-defense against pathogens as the innate immune system, are associated with the progression of inflammatory diseases in response to host-derived DNA, including mitochondrial DNA (mtDNA). Furthermore, recent studies suggest that DNA-sensing mechanisms induce type I interferon in chronic obstructive pulmonary diseases (COPD), usually caused by cigarette smoking. The body possesses several types of DNA sensors. Toll-like receptor 9 (TLR9), a nucleic acid-sensing TLR that recognizes DNA fragments in the endosomes. In addition, stimulator of interferon genes (STING) recognizes cyclic GMP-AMP (cGAMP) generated from DNA fragments in the cytosol. Numerous previous studies have demonstrated that DNA sensors activated by DNA fragments derived from pathogens contribute to self-defense by activating the innate immune system. Therefore, this review describes the role of these DNA sensors in the development of lifestyle-related diseases.